DNA Barcoding of Tabanids (Diptera: Tabanidae) from Veracruz, Mexico, with Notes on Morphology and Taxonomy - Julia J. Alavez-Chávez; Ana C. Montes de Oca-Aguilar; Sokani Sánchez-Montes; Sergio Ibáñez-Bernal; Herón Huerta-Jiménez; Dora Romero-Salas; Anabel Cruz-Romero; Mariel Aguilar-Domínguez (Taxonomy)
(1) Background: Tabanids are one of the most neglected and difficult-to-identify groups within the order Diptera despite their medical–veterinary importance. Since 2010, DNA barcoding has proved to be a promising method for the identification of horseflies in the Old World, but until now it had explored little with regards to Neotropical species. In Mexico, faunal studies continue to be focused on certain regions of the country, which has limited the generation of taxonomic keys. Here, we employed the DNA barcoding approach to contribute to the knowledge of horsefly species in one of the least explored biogeographic provinces in Mexico, the state of Veracruz. (2) Methods: Tabanids were collected at two localities using Malaise traps during two seasons. With a sampling effort of 300 h per trap per site, a total of 22 specimens were collected and identified using taxonomic keys and partial amplification and sequencing of the mitochondrial gene cytochrome c oxidase subunit 1 (COI). (3) Results: Five species of the Tabanus genus were identified through taxonomic keys, and three of these species were confirmed through molecular analyses: T. oculus, T. commixtus, and T. pungens. (4) Conclusions: This is the first contribution of the sequence data of the Tabanidae family for Mexico and demonstrates that DNA barcoding is a vital tool for the recognition of Neotropical species.